Kebijakan Pemerintah Dalam Mendukung Ekonomi Kreatif - Hermawan, Herawati; Rahmadian, Ira (CV. Era Digital Nusantara, 2024)
This research aims to discuss government policies in supporting the creative economy. The method used is library research, data collection by searching for sources and constructing from various sources such as books, journals, and existing researches. This research discusses government policies in supporting the creative economy in Indonesia. . The government has taken strategic steps to strengthen the creative economy sector, including the establishment of the Creative Economy Agency (Bekraf) and the provision of fiscal incentives. In addition, the government also focuses on infrastructure development, education, legal protection, digitization of the creative economy ecosystem and national economic recovery programs. This support is expected to make the creative economy sector continue to develop and contribute significantly to the country's economic growth. Keywords: Government Policy, Creative Economy